Impact of high-altitude exposure on cerebral lobe functions in climbers: insights from the Nepali Himalayas - Dhungel, Sunil; Rana, Shavana R. L.; Neopane, Arun Kumar; Mahat, Barun; Shrestha, Bipin Kumar; Rajaure, Yesha Shree; Thapa, Bikalp; Phuyal, Naveen; Manandhar, Naresh; Shrestha, Udaya; Parajuli, Suraj; Amatya, Taraman (Frontiers in Systems Neuroscience, 2025)
IntroductionHigh-altitude environments challenge cognitive function due to hypoxia, yet their specific effects on cerebral lobe functions remain unclear. This study examines the impact of high-altitude exposure on frontal, parietal, temporal, and occipital lobes in climbers in the Nepali Himalayas, aiming to enhance understanding of altitude-related cognitive decline.MethodsA cross-sectional cohort study was conducted with 76 participants, including 46 non-selected individuals (NOSCL) and 30 selected climbers divided into Everest (EMCL, n = 12), Kanchanjanga (KMCL, n = 9), and Manaslu (MMCL, n = 9) groups. Cognitive function tests (CFT) assessed cerebral lobe function at altitudes ranging from 800 to 5,500 meters using a non-invasive neuropsychological battery.ResultsSignificant altitude-related declines were observed in frontal lobe function, particularly in the Visual Stroop test at 800 meters (75%, p < 0.001) and 2,700 meters (86.1%, p < 0.001). Attention scores also decreased at 800 meters (94.4%, p = 0.002). No significant changes were found in parietal, temporal, or occipital lobe functions. The Manaslu climb presented greater cognitive challenges than Everest or Kanchanjanga, with reduced attention and social cognition scores at 4,800 meters (p = 0.145).DiscussionThe findings indicate that frontal lobe functions are particularly vulnerable to hypoxia at high altitudes. The results support the necessity of region-specific cognitive testing for high-altitude risk assessments. Further research should explore long-term cognitive effects and mitigation strategies for climbers exposed to extreme altitude conditions.